Ni2P / 1T-WS2 / ZnIn2S4 composite catalyst, its preparation method and application
Patent Information
- Application Number
- CN202411087345.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-08-09
AI Technical Summary
目前,大多数助催化剂负载的研究都集中在单一助催化剂的发展上,虽然一定程度上提高了光催化性能,但其活性仍远未令人满意
[0028]本发明Ni2P/1T-WS2/ZnIn2S4三元双助催化剂体系,镶嵌在ZnIn2S4和Ni2P之间金属相1T-WS2与ZnIn2S4形成莫特肖特基界面可有效加速电荷的传递和分离。助催化剂Ni2P引入一方面可有效捕获从1T-WS2传递而来的电子,提供多电荷转移转移通道,进一步提升了电荷的分离性能;另一方面还可为光还原反应提供了大量的活性位点,从而使得Ni2P/1T-WS2/ZnIn2S4双助催化剂的光催化H2O2析出性能得到极大提升。
Smart Images

Figure CN118976519B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic materials technology, specifically relating to a Ni2P / 1T-WS2 / ZnIn2S4 composite catalyst, its preparation method, and its application in the photocatalytic preparation of H2O2. Background Technology
[0002] As a clean and mild oxidant, hydrogen peroxide (H2O2) has many advantages, such as the highest content of reactive oxygen species, excellent efficacy over a wide pH range, and non-toxic byproducts (only water / O2 is produced). Currently, H2O2 is widely used in various industrial fields, such as bleaching, mining and metal processing, detergent applications, wastewater treatment, and the synthesis of chemical organic compounds. More importantly, H2O2 has perfect solubility in water, providing a simpler and safer method for storage and transportation. Industrially, H2O2 is produced on a large scale via the energy-intensive anthraquinone process.
[0003] Unlike the traditional anthraquinone method, photocatalytic H2O2 production is a potential solar-driven technology that has attracted widespread attention due to its advantages such as low energy consumption, greenness, and environmental friendliness. The core of photocatalytic H2O2 production technology is the catalyst, among which ZnIn2S4, as a typical semiconductor photocatalyst, is considered one of the most promising materials for H2O2 production due to its suitable conduction and valence band positions, ease of preparation, low toxicity, and excellent photoelectric properties. However, the photoresponse range of pure ZnIn2S4 in practical applications is limited to the ultraviolet light region, and its rapid recombination of photogenerated electrons and holes, as well as photocorrosion, severely affect its photocatalytic performance. To improve the photocatalytic performance of ZnIn2S4, various strategies have been explored for its modification, including morphology control, heterojunction construction, metal or non-metal element doping, and co-catalyst loading.
[0004] Among numerous modification strategies, co-catalyst loading not only improves the separation efficiency of photogenerated electrons and holes but also provides more reactive sites for the photoreaction, thereby enhancing the photoactivity of the catalyst. Currently, most research on co-catalyst loading focuses on the development of single co-catalysts. Although this has improved photocatalytic performance to some extent, its activity remains far from satisfactory. Summary of the Invention
[0005] To overcome the aforementioned technical deficiencies, this invention provides a simple and easily implemented dual-co-catalyst Ni2P / 1T-WS2 / ZnIn2S4. Using ZnIn2S4 nanosheets as the main catalyst, this invention successfully synthesizes metallic 1T-WS2 nanospheres and Ni2P nanoparticles with ZnIn2S4 nanosheets through a simple ultrasonic composite strategy to prepare a dual-co-catalyst photocatalytic system and apply it to the photocatalytic preparation of H2O2. In this invention, the Motter-Schottky interface formed by the metallic 1T-WS2 and ZnIn2S4 effectively accelerates charge transfer and separation; while the introduction of the co-catalyst Ni2P effectively captures electrons transferred from 1T-WS2, providing multiple charge transfer channels and further improving charge separation performance; on the other hand, it also provides a large number of active sites for the photoreduction reaction, thereby effectively improving the H2O2 precipitation kinetics. Based on these advantages, the Ni2P / 1T-WS2 / ZnIn2S4 dual-co-catalyst system prepared in this invention shows good application in the photocatalytic preparation of H2O2.
[0006] The Ni2P / 1T-WS2 / ZnIn2S4 composite catalyst of this invention is characterized by the following structural features: the mass ratio of ZnIn2S4, 1T-WS2, and Ni2P in the catalyst is 1:0.01-0.2:0.001-0.1; ZnIn2S4 has a nanosheet structure, 1T-WS2 has a nanoflower structure, and Ni2P has a nanoparticle structure; the XRD patterns show high XRD values at 21.58°, 27.69°, 30.45°, 39.77°, 52.47°, and 55.58°. Strong diffraction peaks are observed; binding energies exist in XPS at 161.45 eV, 162.65 eV, 444.94 eV, 452.49 eV, 1021.26 eV, 1044.38 eV, 31.88 eV, 33.14 eV, 33.91 eV, 35.34 eV, 37.60 eV, 129.55 eV, 130.25 eV, 853.19 eV, 872.64 eV, 856.61 eV, 877.07 eV, and 862.37 eV.
[0007] from Figure 1The XRD crystal structure of the catalyst clearly shows that the ZnIn2S4 sample exhibits six strong diffraction peaks at 21.58°, 27.69°, 30.45°, 39.77°, 52.47°, and 55.58°, consistent with the standard XRD pattern of hexagonal ZnIn2S4 (JCPDS No. 89-3963). The 1T-WS2 pattern shows three diffraction peaks at 9.3°, 18.3°, and 31.9°, belonging to the (002), (004), and (006) crystal planes of 1T-WS2, respectively. The XRD peak shape of pure Ni2P is consistent with the standard XRD pattern of hexagonal Ni2P (PDF#03-0953), indicating that the prepared Ni2P has high purity and contains no other impurities. The disappearance of the WS2 peak at 9.3° in the three-component Ni2P / 1T-WS2 / ZnIn2S4 composite sample is attributed to the influence of Ni2P or the high dispersion of the sample. Compared with the 14.32° (002) peak of 2H-WS2, the new (002) peak of 1T-WS2 has shifted to the 9.3° position, proving that the metallic phase 1T-WS2 has been prepared.
[0008] from Figure 2 From Ni2P / 1T-WS2 / ZnIn2S4XPS, we can see that: S2p 3 / 2 and S2p 1 / 2 The binding energies are 161.45 eV and 162.65 eV; In 3d 5 / 2 and In 3d 3 / 2 The binding energies are 444.94 eV and 452.49 eV; Zn 2p 3 / 2 and Zn 2p 1 / 2 The binding energies are 1021.26 eV and 1044.38 eV; 4f 7 / 2 -1T and 4f 5 / 2 The binding energies for -1T are 31.88 eV and 33.14 eV, respectively, and for 4f... 7 / 2 -2H and 4f 5 / 2 The -2H binding energies are 33.91 eV and 35.34 eV, W 6+ The corresponding binding energy is 37.60 eV; P 2p 3 / 2 and P 2p 1 / 2 The binding energies are 129.55 eV and 130.25 eV, with a characteristic peak at 133.45 eV corresponding to the PO bond; Ni 2p 3 / 2 and Ni 2p 1 / 2 The binding energies are 853.19 eV and 872.64 eV, and the characteristic peak at 862.37 eV is a satellite peak. The spectrum shows that five elements, S, In, Zn, W, Ni, and P, are present simultaneously, and no other impurity peaks were detected, indicating that a high-purity ternary complex was successfully prepared.
[0009] from Figure 3 The SEM morphology of the samples shows that the ZnIn2S4 sample exhibits a three-dimensional, interwoven, ultrathin nanosheet structure, the 1T-WS2 sample is a nanosphere with a diameter of about 5μm, and the Ni2P sample shows an irregular, coral-like accumulation of nanoparticles.
[0010] from Figure 4 TEM and HRTEM images clearly show that several different lattice fringes are interwoven. The ZnIn2S4 lattice spacings of 0.321 nm and 0.423 nm correspond to the (001) and (006) crystal planes, respectively. 1T-WS2 has a wider lattice spacing of 0.932 nm, corresponding to its (002) crystal plane. Ni2P lattice fringes are also clearly visible, with a lattice spacing of 0.221 nm corresponding to its (111) crystal plane. The TEM and HRTEM images indicate that ZnIn2S4, 1T-WS2, and Ni2P have been successfully composited.
[0011] from Figure 5 The study of charge separation and transfer effects in PL samples revealed that the spectral peak intensities of the two-component composite materials 1T-WS2 / ZnIn2S4, Ni2P / ZnIn2S4, and the three-component composite material Ni2P / 1T-WS2 / ZnIn2S4 were significantly weaker than those of pure ZnIn2S4. Among them, the spectral intensity of the three-component composite material Ni2P / 1T-WS2 / ZnIn2S4 was the weakest. This indicates that both the co-catalysts 1T-WS2 and Ni2P can rapidly transfer photogenerated electrons when combined with ZnIn2S4. However, when Ni2P is combined with 1T-WS2 / ZnIn2S4, the synergistic effect of the co-catalysts 1T-WS2 and Ni2P further enhances the ability of the co-catalysts 1T-WS2 and Ni2P to transfer photogenerated electrons.
[0012] from Figure 6 The transient current spectrum shows that ZnIn2S4 exhibits a low current density, indicating that only a small number of photogenerated electrons are involved in the transfer and separation process. Compared with ZnIn2S4, the transient photocurrent intensities of the two-component composite samples 1T-WS2 / ZnIn2S4 and Ni2P / ZnIn2S4 are significantly increased, and the current intensity of the three-component composite sample Ni2P / 1T-WS2 / ZnIn2S4 is the highest. This further proves that the introduction of 1T-WS2 and Ni2P as dual co-catalysts can rapidly transfer electrons on the conduction band of ZnIn2S4 and accelerate the separation of photogenerated electrons and holes.
[0013] from Figure 7The electrochemical impedance spectroscopy shows that the Nyquist radii are in the following order: ZnIn2S4 > 1T-WS2 / ZnIn2S4 > Ni2P / ZnIn2S4 > Ni2P / 1T-WS2 / ZnIn2S4. This indicates that the introduction of 1T-WS2 and Ni2P cocatalysts can effectively reduce the interfacial charge transfer resistance, and photogenerated electrons and holes can be separated rapidly. At the same time, the synergistic effect of 1T-WS2 and Ni2P can further accelerate the separation rate of photogenerated electrons and holes, and improve the photocatalytic H2O2 production performance.
[0014] from Figure 8 The photocatalytic H2O2 production experiments show that pure ZnIn2S4 exhibits poor H2O2 production performance due to rapid charge carrier recombination. The H2O2 production performance of the binary composite photocatalyst obtained by loading 1T-WS2 or Ni2P onto ZnIn2S4 is improved. The H2O2 production performance of the ternary composite photocatalyst obtained by simultaneously loading 1T-WS2 and Ni2P onto ZnIn2S4 is the highest, indicating that the synergistic effect of 1T-WS2 and Ni2P can greatly improve the H2O2 production performance of ZnIn2S4.
[0015] The method for preparing the Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst of the present invention includes the following steps:
[0016] 1) Dissolve zinc chloride, indium chloride, and thioacetamide in an ethanol aqueous solution, and then subject the solution to a hydrothermal reaction at 160-200℃ to obtain pale yellow ZnIn2S4 nanosheets.
[0017] Furthermore, in the above technical solution, the molar ratio of zinc chloride, indium chloride and thioacetamide is 1:2:4.
[0018] 2) Dissolve tungsten chloride and thioacetamide in N,N-dimethylformamide, and carry out hydrothermal reaction of the solution at 180-220℃ to obtain black 1T-WS2 nanoflower balls.
[0019] Furthermore, in the above technical solution, the molar ratio of tungsten chloride to thioacetamide is 1:10.
[0020] 3) Dissolve red phosphorus and nickel chloride in deionized water, and carry out hydrothermal reaction of the solution at 140-180℃ to obtain black Ni2P nanoparticles.
[0021] Furthermore, in the above technical solution, the molar ratio of red phosphorus to nickel chloride is 1:6.
[0022] 4) Disperse the ZnIn2S4 nanosheets obtained in step 1) and the 1T-WS2 nanoflowers obtained in step 2) into an aqueous solution and perform ultrasonic stirring treatment to obtain a 1T-WS2 / ZnIn2S4 composite photocatalyst.
[0023] Furthermore, in the above technical solution, the mass ratio of ZnIn2S4 to 1T-WS2 is 1:0.01-0.2.
[0024] 5) Disperse the Ni2P obtained in step 3) and the 1T-WS2 / ZnIn2S4 complex obtained in step 4) into an aqueous solution and perform ultrasonic stirring to obtain the Ni2P / 1T-WS2 / ZnIn2S4 ternary dual co-catalyst system.
[0025] Furthermore, in the above technical solution, the mass ratio of ZnIn2S4 to 1T-WS2 is 1:0.001-0.1.
[0026] Photocatalytic production of H2O2 operating conditions: Light source: 300W xenon lamp; Catalyst: 100mg; Deionized water: 90mL; Isopropanol: 10mL. Figure 8 The data shows that the photocatalytic production rate of H2O2 from pure ZnIn2S4 is 0.65 mmol / g. -1 h -1 The photocatalytic production rate of H2O2 from Ni2P / ZnIn2S4 was 2.16 mmol g. -1 h -1 The photocatalytic production rate of H2O2 using 1T-WS2 / ZnIn2S4 was 2.84 mmol g. -1 h -1 The photocatalytic production rate of H2O2 from Ni2P / 1T-WS2 / ZnIn2S4 was 6.34 mmol g. -1 h -1 It exhibits significantly enhanced photocatalytic H2O2 production performance.
[0027] Beneficial effects of this invention:
[0028] The present invention relates to a Ni2P / 1T-WS2 / ZnIn2S4 ternary dual co-catalyst system. The 1T-WS2 metal phase embedded between ZnIn2S4 and Ni2P forms a Motter-Schottky interface with ZnIn2S4, effectively accelerating charge transfer and separation. The introduction of the co-catalyst Ni2P effectively captures electrons transferred from 1T-WS2, providing multiple charge transfer channels and further enhancing charge separation performance. Furthermore, it provides numerous active sites for the photoreduction reaction, thereby significantly improving the photocatalytic H2O2 precipitation performance of the Ni2P / 1T-WS2 / ZnIn2S4 dual co-catalyst. Attached Figure Description
[0029] Figure 1 The XRD patterns of ZnIn2S4, 1T-WS2, Ni2P, Ni2P / ZnIn2S4, 1T-WS2 / ZnIn2S4 and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention;
[0030] Figure 2 XPS spectra of ZnIn2S4, 1T-WS2, Ni2P, and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention;
[0031] Figure 3 The images show SEM images of ZnIn2S4, 1T-WS2, Ni2P, and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention.
[0032] Figure 4 The images show TEM(a) and HRTEM(b) images of Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention.
[0033] Figure 5 The PL spectra of ZnIn2S4, 1T-WS2 / ZnIn2S4, Ni2P / ZnIn2S4, and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention;
[0034] Figure 6 The transient current spectra of ZnIn2S4, 1T-WS2 / ZnIn2S4, Ni2P / ZnIn2S4, and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention are shown.
[0035] Figure 7 Electrochemical impedance spectroscopy of ZnIn2S4, 1T-WS2 / ZnIn2S4, Ni2P / ZnIn2S4, and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention;
[0036] Figure 8 The image shows the photocatalytic H2O2 production effect of ZnIn2S4, 1T-WS2 / ZnIn2S4, Ni2P / ZnIn2S4, and Ni2P / 1T-WS2 / ZnIn2S4 prepared in Example 1 of this invention. Detailed implementation method:
[0037] The present invention is further described below with reference to embodiments. It should be noted that the present invention is not limited to the embodiments described below.
[0038] Example 1
[0039] 1) Preparation of ZnIn2S4 nanosheets: 15 mL of deionized water and 15 mL of anhydrous ethanol were poured into a 50 mL beaker to prepare a 50% ethanol aqueous solution. While stirring, 0.0545 g of ZnCl2, 0.1769 g of InCl3, and 0.2404 g of CH3CSNH2 (TAA) were added sequentially. The mixture was stirred at room temperature for 10 min. The solution, once clear, was transferred to a 50 mL polytetrafluoroethylene high-pressure reactor and kept in an oven at 180 °C for 24 h. After the reactor cooled naturally to room temperature, it was filtered using a 1000 mL vacuum filtration flask. During filtration, the sample was washed three times with deionized water and three times with anhydrous ethanol. The resulting yellow solid sample was then transferred to a vacuum drying oven at 60 °C and dried for 12 h. The resulting pale yellow ZnIn2S4 nanosheets were obtained by grinding.
[0040] 2) Preparation of 1T-WS2 nanoflower balls: 0.7932g WCl6 and 1.5026g TAA were weighed and added to 60mL N,N-dimethylformamide (DMF) and stirred vigorously for 1h. Then, the mixture was transferred to an ultrasonic machine and sonicated for 1h. Subsequently, it was transferred to a 100mL polytetrafluoroethylene high-pressure reactor and kept in an oven at 200℃ for 24h. After the reactor cooled naturally to room temperature, it was filtered with a 1000mL vacuum filtration flask. During the filtration process, the sample was washed multiple times with anhydrous ethanol. The resulting black solid sample was then placed in a vacuum drying oven at 60℃ for 12h to obtain black powdery solid 1T-WS2 nanoflower balls.
[0041] 3) Preparation of Ni2P nanoparticles: 0.094 g NiCl2·6H2O and 0.049 g red phosphorus were weighed and added sequentially to 30 mL of 30% ethanol solution. The mixture was stirred for 30 min and then sonicated for 1 h. The solution was then transferred to a 100 mL polytetrafluoroethylene reactor and kept in an oven at 150 °C for 12 h. After the reaction mixture cooled naturally to room temperature, it was washed several times with deionized water and anhydrous ethanol. The resulting black solid sample was then placed in a vacuum drying oven at 60 °C for 12 h to obtain black powdery Ni2P nanoparticles.
[0042] 4) Preparation of 1T-WS2 / ZnIn2S4 composite photocatalyst: Take 5.0 mg of 1T-WS2 obtained in step 2) and disperse it in 50 mL of deionized water. After sonication for 30 min, the dispersion is uniform. Then add 0.1 g of ZnIn2S4 sample, continue sonication for 90 min and stir vigorously at room temperature for 10 h. Wash three times with deionized water and anhydrous ethanol respectively. Then keep in a vacuum drying oven at 60℃ for 12 h to obtain composite sample 1T-WS2 / ZnIn2S4.
[0043] 5) Preparation of Ni2P / 1T-WS2 / ZnIn2S4 ternary composite photocatalyst: Take 1.0 mg of Ni2P obtained in step 3) and disperse it in 50 mL of deionized water and sonicate for 30 min. Take 0.1 g of the 1T-WS2 / ZnIn2S4 two-component composite sample obtained in step 4) and sonicate for another 90 min. Stir vigorously at room temperature for 10 h and wash three times with deionized water and anhydrous ethanol respectively. Then keep it in a vacuum drying oven at 60℃ for 12 h to obtain the dual co-catalyst Ni2P / 1T-WS2 / ZnIn2S4 system.
[0044] Example 2
[0045] 1) Preparation of ZnIn2S4 nanosheets: 15 mL of deionized water and 15 mL of anhydrous ethanol were poured into a 50 mL beaker to prepare a 50% ethanol aqueous solution. While stirring, 0.0545 g of ZnCl2, 0.1769 g of InCl3, and 0.2404 g of CH3CSNH2 (TAA) were added sequentially. The mixture was stirred at room temperature for 10 min. The solution, once clear, was transferred to a 50 mL polytetrafluoroethylene high-pressure reactor and kept in a 160 °C oven for 24 h. After the reactor cooled naturally to room temperature, it was filtered using a 1000 mL vacuum filtration flask. During filtration, the sample was washed three times with deionized water and three times with anhydrous ethanol. The resulting yellow solid sample was then transferred to a vacuum drying oven and dried at 60 °C for 12 h. The resulting pale yellow ZnIn2S4 nanosheets were obtained by grinding.
[0046] 2) Preparation of 1T-WS2 nanoflower balls: 0.7932g WCl6 and 1.5026g TAA were weighed and added to 60mL N,N-dimethylformamide (DMF) and stirred vigorously for 1h. Then, the mixture was transferred to an ultrasonic machine and sonicated for 1h. Subsequently, it was transferred to a 100mL polytetrafluoroethylene high-pressure reactor and kept in an oven at 180℃ for 24h. After the reactor cooled naturally to room temperature, it was filtered with a 1000mL vacuum filtration flask. During the filtration process, the sample was washed multiple times with anhydrous ethanol. The resulting black solid sample was then placed in a vacuum drying oven at 60℃ for 12h to obtain black powdery solid 1T-WS2 nanoflower balls.
[0047] 3) Preparation of Ni2P nanoparticles: 0.094 g NiCl2·6H2O and 0.049 g red phosphorus were weighed and added sequentially to 30 mL of 30% ethanol solution. The mixture was stirred for 30 min and then sonicated for 1 h. The solution was then transferred to a 100 mL polytetrafluoroethylene reactor and kept in an oven at 140 °C for 12 h. After the reaction mixture cooled naturally to room temperature, it was washed several times with deionized water and anhydrous ethanol. The resulting black solid sample was then placed in a vacuum drying oven at 60 °C for 12 h to obtain black powdery Ni2P nanoparticles.
[0048] 4) Preparation of 1T-WS2 / ZnIn2S4 composite photocatalyst: Take 1.0 mg of 1T-WS2 obtained in step 2) and disperse it in 50 mL of deionized water. After sonicating for 30 min, the dispersion is uniform. Then add 0.1 g of ZnIn2S4 sample, continue sonicating for 90 min and stirring vigorously at room temperature for 10 h. Wash three times with deionized water and anhydrous ethanol respectively. Then keep in a vacuum drying oven at 60℃ for 12 h to obtain composite sample 1T-WS2 / ZnIn2S4.
[0049] 5) Preparation of Ni2P / 1T-WS2 / ZnIn2S4 ternary composite photocatalyst: Take 0.1 mg of Ni2P obtained in step 3) and disperse it in 50 mL of deionized water and sonicate for 30 min. Take 0.1 g of the 1T-WS2 / ZnIn2S4 two-component composite sample obtained in step 4) and sonicate for another 90 min. Stir vigorously at room temperature for 10 h and wash three times with deionized water and anhydrous ethanol respectively. Then keep it in a vacuum drying oven at 60℃ for 12 h to obtain the dual co-catalyst Ni2P / 1T-WS2 / ZnIn2S4 system.
[0050] Example 3
[0051] 1) Preparation of ZnIn2S4 nanosheets: 15 mL of deionized water and 15 mL of anhydrous ethanol were poured into a 50 mL beaker to prepare a 50% ethanol aqueous solution. While stirring, 0.0545 g of ZnCl2, 0.1769 g of InCl3, and 0.2404 g of CH3CSNH2 (TAA) were added sequentially. The mixture was stirred at room temperature for 10 min. The solution, after reaching a clear state, was transferred to a 50 mL polytetrafluoroethylene high-pressure reactor and kept in a 200 °C oven for 24 h. After the reactor cooled naturally to room temperature, it was filtered using a 1000 mL vacuum filtration flask. During filtration, the sample was washed three times with deionized water and three times with anhydrous ethanol. The resulting yellow solid sample was then transferred to a vacuum drying oven and dried at 60 °C for 12 h. The resulting pale yellow ZnIn2S4 nanosheets were obtained by grinding.
[0052] 2) Preparation of 1T-WS2 nanoflower balls: 0.7932g WCl6 and 1.5026g TAA were weighed and added to 60mL N,N-dimethylformamide (DMF) and stirred vigorously for 1h. Then, the mixture was transferred to an ultrasonic machine and sonicated for 1h. Subsequently, it was transferred to a 100mL polytetrafluoroethylene high-pressure reactor and kept in an oven at 220℃ for 24h. After the reactor cooled naturally to room temperature, it was filtered with a 1000mL vacuum filtration flask. During the filtration process, the sample was washed multiple times with anhydrous ethanol. The resulting black solid sample was then placed in a vacuum drying oven at 60℃ for 12h to obtain black powdery solid 1T-WS2 nanoflower balls.
[0053] 3) Preparation of Ni2P nanoparticles: 0.094 g NiCl2·6H2O and 0.049 g red phosphorus were weighed and added sequentially to 30 mL of 30% ethanol solution. The mixture was stirred for 30 min and then sonicated for 1 h. The solution was then transferred to a 100 mL polytetrafluoroethylene reactor and kept in an oven at 180 °C for 12 h. After the reaction mixture cooled naturally to room temperature, it was washed several times with deionized water and anhydrous ethanol. The resulting black solid sample was then placed in a vacuum drying oven at 60 °C for 12 h to obtain black powdery Ni2P nanoparticles.
[0054] 4) Preparation of 1T-WS2 / ZnIn2S4 composite photocatalyst: Take 20mg of 1T-WS2 obtained in step 2) and disperse it in 50mL of deionized water. After sonication for 30min, the dispersion is uniform. Then add 0.1g of ZnIn2S4 sample, continue sonication for 90min and stir vigorously at room temperature for 10h. Wash three times with deionized water and anhydrous ethanol respectively. Then keep in a vacuum drying oven at 60℃ for 12h to obtain composite sample 1T-WS2 / ZnIn2S4.
[0055] 5) Preparation of Ni2P / 1T-WS2 / ZnIn2S4 ternary composite photocatalyst: Take 10 mg of Ni2P obtained in step 3) and disperse it in 50 mL of deionized water and sonicate for 30 min. Take 0.1 g of the 1T-WS2 / ZnIn2S4 two-component composite sample obtained in step 4) and sonicate for another 90 min. Stir vigorously at room temperature for 10 h and wash three times with deionized water and anhydrous ethanol respectively. Then keep it in a vacuum drying oven at 60℃ for 12 h to obtain the dual co-catalyst Ni2P / 1T-WS2 / ZnIn2S4 system.
[0056] Example 4: Photocatalytic H2O2 Production Experiment
[0057] 100 mg of catalyst was uniformly dispersed in a mixed solution containing 10 mL of isopropanol and 90 mL of water. After ultrasonic treatment for 10 min, oxygen was continuously introduced and the mixture was stirred in the dark for 30 min. A 300 W xenon lamp was used as the light source for the photocatalytic production of H₂O₂. Figure 8 It can be seen that the photocatalytic H2O2 evolution rate of pure ZnIn2S4 is 0.65 mmol g. -1 h -1 The photocatalytic H2O2 evolution rate using the Ni2P / 1T-WS2 / ZnIn2S4 dual co-catalyst system obtained in Example 1 reached 6.34 mmol g. -1 h -1 It exhibits significantly enhanced photocatalytic H2O2 extraction performance.
[0058] The composite photocatalysts prepared using Examples 2-3 achieved similar hydrogen peroxide production effects.
[0059] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from its principles, and all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst, characterized in that: The mass ratio of ZnIn2S4, 1T-WS2, and Ni2P in the catalyst is 1:0.01-0.2:0.001-0.
1. ZnIn2S4 has a nanosheet structure, 1T-WS2 has a nanoflower-like structure, and Ni2P has a nanoparticle structure. The XRD pattern shows strong diffraction peaks at 21.58°, 27.69°, 30.45°, 39.77°, 52.47°, and 55.58°. The XPS pattern shows peaks at 161.45 eV, 162.65 eV, 444.94 eV, 452.49 eV, 1021.26 eV, 1044.38 eV, 31.88 eV, 33.14 eV, 33.91 eV, 35.34 eV, 37.60 eV, and 129.55 eV. Binding energies exist at eV, 130.25 eV, 853.19 eV, 872.64 eV, 856.61 eV, 877.07 eV, and 862.37 eV; wherein the Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst is prepared by the following method: 1) Dissolve zinc chloride, indium chloride, and thioacetamide in a 50% ethanol aqueous solution, and carry out a hydrothermal reaction at 160-200℃ to obtain pale yellow ZnIn2S4 nanosheets. 2) Dissolve tungsten chloride and thioacetamide in N,N-dimethylformamide, and carry out hydrothermal reaction of the solution at 180-220℃ to obtain black 1T-WS2 nanoflower balls; 3) Dissolve red phosphorus and nickel chloride in deionized water, and carry out hydrothermal reaction of the solution at 140-180℃ to obtain black Ni2P nanoparticles. 4) Disperse the ZnIn2S4 nanosheets obtained in step 1) and the 1T-WS2 nanoflowers obtained in step 2) into an aqueous solution and perform ultrasonic stirring to obtain the 1T-WS2 / ZnIn2S4 composite. 5) The Ni2P nanoparticles obtained in step 3) and the 1T-WS2 / ZnIn2S4 composite obtained in step 4) are dispersed in an aqueous solution and subjected to ultrasonic stirring to obtain a Ni2P / 1T-WS2 / ZnIn2S4 ternary dual-auxiliary composite photocatalyst.
2. The Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 1, characterized in that: In step 1), the molar ratio of zinc chloride, indium chloride, and thioacetamide is 1:2:
4.
3. The Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 1, characterized in that: In step 2), the molar ratio of tungsten chloride to thioacetamide is 1:
10.
4. The Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 1, characterized in that: In step 3), the molar ratio of red phosphorus to nickel chloride is 1:
6.
5. The Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 1, characterized in that: In step 4), the mass ratio of ZnIn2S4 to 1T-WS2 is 1:0.01-0.
2.
6. The Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 1, characterized in that: In step 5), the mass ratio of 1T-WS2 / ZnIn2S4 to Ni2P is 1:0.001-0.
1.
7. The Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 1, characterized in that: The composite photocatalyst is a dual co-catalyst system that forms the Mott-Schottky junction interface.
8. The application of the Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst as described in claim 1 in the photocatalytic preparation of H2O2.
9. The application of the Ni2P / 1T-WS2 / ZnIn2S4 composite photocatalyst according to claim 8 in the photocatalytic preparation of H2O2, characterized in that: The operating conditions were as follows: 300 W xenon lamp as the light source; 100 mg catalyst; 90 mL deionized water; and 10 mL isopropanol.